Characterization of different heat mitigation strategies in landscape to fight against heat island and improve thermal comfort in hot–humid climate (Part I): Measurement and modelling. (July 2017) - Zhao, T.F.; Fong, K.F.
Highlights: Thermal performances of different heat mitigation strategies (HMSs) in landscape was investigated by field measurement. The differences in air temperature and mean radiant temperature could reach 4.5 and 32 °C within campus landscape. Relationship between microclimate and different HMSs in landscape was identified. A landscape model was developed with ENVI-met V4. Abstract: This study aims to consolidate and characterize the cooling potentials of heat mitigation strategies (HMSs) in landscape from both combating urban heat island (UHI) and alleviating human heat stress. This is Part I of the study, which focuses on measurement and modelling of all the possible HMSs (vegetation, albedo and water body) in landscape. The field measurement included ground level greening, different albedo pavements and water pools, which can be categorized into green, grey and blue areas. Through the microclimate simulation tool ENVI-met V4, a landscape model was developed and its performance was assessed. It was found that the variations of air temperature and mean radiant temperature within a campus landscape would be large, up to 4.5 and 32 °C respectively. The green and blue areas showed certain heat mitigation potential, but the grey areas had the possibility to generate uncomfortable thermal environment. The close relationship between microclimate and different HMSs in landscape was identified. The landscape model was capable of reproducing the main features of temporal and spatial distributions of intra-urban microclimate. Hence, the validated settings of such landscape model would be passed on for prediction of mitigation potentials of different HMSs in Part II of this study.